Safety and efficacy of wiping lid margins with lid hygiene shampoo using the “eye brush”, a novel lid hygiene item, in healthy subjects: a pilot study - Tanabe, Hirotaka (BMC Ophthalmol, 2019)
BACKGROUND: To evaluate the safety and efficacy of using a lid hygiene brush prototype to wipe the lid margins with lid hygiene shampoo in subjects with normal meibomian glands. METHODS: Twelve eyes of 6 subjects were all evaluated just before and after wiping lid margins using 1) tap water alone, 2) Eye Shampoo, 3) Eye Brush, or 4) both products, each during a different week. The results after using both products twice daily for 1 month were also evaluated. Wiping efficacy was determined by post-wiping scores for the remaining fluorescein-stained 0.3% Tarivid ointment fully applied to eyelids and lid margins under microscopic view illuminated by blue light just after performing each of the four lid hygiene methods described above. RESULTS: No significant deterioration in ocular conditions occurred. Eyestrain, eye discharge, and dryness decreased with tap water (P = 0.020), Eye Shampoo (P = 0.036), and Eye Brush (P = 0.014), respectively. Sensations of eye discharge increased after 1 month of using both products (P = 0.042). The wiping efficacy of Eye Brush, Eye Shampoo or both was significantly greater than that of tap water alone (two-sided test, P = 0.003, 0.003, 0.002), and using both significantly increased efficacy above Eye Shampoo use alone (one-sided test, P = 0.009). CONCLUSIONS: Wiping lid margins using Eye Brush enhanced the cleansing power of Eye Shampoo. A daily healthcare routine using both products could be a safe and effective option for daily lid hygiene. TRIAL REGISTRATION: UMIN000016905. Registration date: March 24, 2015; the study was prospectively registered. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12886-019-1052-y) contains supplementary material, which is available to authorized users.